Search engine optimisation elements' effect on website visibility: the Western Cape real estate SMME sector - Visser, Eugene Bourbon (Cape Peninsula University of Technology, 2014)
Thesis submitted in fulfilment of the requirements for the degree Magister Technologiae in Information Technology in the Faculty of Informatics and Design 2006 === The primary objective of this research project was to determine whether search engine optimisation elements as specified in the Chambers model, affect real estate website visibility. In South Africa, real estate companies predominantly function as SMMEs and are therefore as vulnerable to failure as any other SMME in the country. In order for SMMEs to reduce the possibility of failure, they need to re-evaluate their use of the Internet, as it could assist in their survival. The traditional company structure is no longer sufficient to ensure market reward. The reality is that users are rapidly adapting to the technology available. The Internet is fast becoming a communication, commerce and marketing medium that is changing business globally. Real estate SMMEs are unable to adapt to e-commerce in its purest form, however, they can make effective use of e-marketing. Static websites are used for that specific purpose. A marketing strategy is imperative to the survival of a company, whereby the firm is able to create and maintain a competitive advantage in a cluttered marketplace. Regrettably, hosting a website on the Internet is not enough. Searchers tend not to view search results beyond the second page - 30 results at the most. It becomes evident that companies should ensure that their own website ranks as high as possible on the search engine result page. This in turn should sufficiently market the company. Search engine optimisation involves designing or modifying websites in order to improve search engine result page ranking. The elements as specified in the Chambers model are extensively elaborated on in the literature analysis. The methodology consisted of two stages - a questionnaire and empirical experiments. A quantitative research approach was adopted for both of these components. The primary objective of the questionnaire was to obtain search phrases from the public when searching for real estate online. The search phrases were then used in the experiments, testing the visibility of predetermined websites, which were based on a pre- post- test control group design methodology. In this instance, the before group consisted of five different websites from five different real estate companies which have been hosted on the Internet for a duration of no less than three months. The Chambers model was used in the development of five new optimised websites, one for each company. The new websites were hosted on the Internet for 27 days, in order to give search engines the opportunity to index them. The results documented were then compared in order to draw a conclusion. A total of 121 key search phrases were obtained. The results from the old and new websites were applied to a process which produced a combination of results known as the ‘quality factor’. The quality factor indicated either a visibility improvement or visibility deterioration with regard to the old and new company’s website. In addition to this, this author compared